The Effect of Bandgap Graded Absorber on the Performance of a-Si1–xGex:H Single-Junction Cells with μc-SiOx:H N-Type Layer - Hung-Jung Hsu; Cheng-Hang Hsu; Chuang-Chuang Tsai (International Journal of Photoenergy)
We reported the effect of bandgap grading of absorbers on the performance of a-Si1−xGex:H cells employing μc-SiOx:H n-layer. The influence of bandgap grading widths extended from the p-layer (the p/i grading) and the n-layer (the i/n grading) to the absorber on the cell performance which were systematically studied. The p/i grading reduced the interface defects and thus improved the VOC. The reduced JSC and FF were presumably due to the degraded hole transport by the potential gradient of p/i grading. Increasing the i/n grading width improved the carrier collection significantly. The EQE, the JSC, and the FF were improved substantially. Bias-dependent EQE revealed that the carrier collection is efficient in the cell employing optimal i/n grading. On the other hand, increasing the i/n grading width was accompanied by the decrease in long-wavelength response which potentially constrained the i/n grading width. Compared to the cell without grading, the a-Si1−xGex:H cells with optimal p/i and i/n grading width improved the efficiency from 5.5 to 7.5%.